Women's Leadership in Improving the Quality of Education in Junior High Schools - Iin Roikhatul Jannah; Rubini (The Faculty of Education and Teaching Training, 2026)
Women’s leadership in Islamic educational institutions has increasingly become part of the broader transformation of school governance and quality development. This study aims to examine the leadership practices of a female principal at SMP Babul Ilmi and to explore their impact on strengthening the school’s quality culture. A qualitative research design was employed, utilizing in-depth interviews, observation, and document analysis. The participants included the principal, teachers, administrative staff, and students. Data were analyzed through processes of reduction, categorization, and verification, supported by source triangulation to ensure credibility and trustworthiness. The findings reveal that female leadership in this context is characterized by the integration of Islamic values, empathetic-participatory communication, and structured, transparent management practices. These approaches contribute to increased teacher engagement, clearer organizational coordination among staff, and a safer, more supportive learning environment for students. Although initial challenges related to gender-based social perceptions were identified, leadership legitimacy gradually developed through consistent performance and managerial competence. The study concludes that leadership effectiveness in Islamic secondary schools is primarily shaped by integrity, professional capacity, and adaptive competence rather than gender identity. This research offers an empirical contribution to the discourse on Islamic educational leadership by presenting a value-based and quality-oriented model of women’s leadership.